A Conflict Reveal Killer Of Death Mystery From The Rich Author In Knives Out Movie (2019): A Sociological Approach - Alifia Wulandari; Abdillah Nugroho (Publikasi Indonesia, 2023)
Literary is reading something literature, forming a critical opinion, or judging someone's criticism based on the theme, figurative language, etc on the library work. The analysis method is by uncovering topics for good understanding. Knives Out movie is a criminal and drama film full of mystery but also the movie that has is a comedy. The type of study in this research uses a Qualitative Descriptive Approach. The research objects of this study are characteristics, mystery, speech act, the main character, the situation, and the story of Knives Out (2019) movie. The object is based on the movie. The data collection technique divided into 4kinds are watching, reading, taking notes, and observation. The sociological Approach is used in the Knives Out movie because there some several social forms example Crime, Family Life, Social Class, Racism, and Inequality.